Rampur Hydropower Project : Land Acquisition, Resettlement and Community Development Practices - Mittal, Rohit; Reddy, I.U.B.; Mensan Gaba, Kwawu (World Bank, Washington, DC, 2014)
SJVN Limited (SJVNL), a mini ratna public sector undertaking of the Government of India (GoI), is implementing the World Bank funded 412 MW run-of-the-river hydro power project at Rampur in Himachal Pradesh, immediately downstream of and in cascade operation with the 1500 MW Nathpa Jhakri Hydroelectric Project (NJHP). Located in Shimla and Kullu districts, the Rampur Project involves the construction of a 15.17 km, 10.5 m of diameter, head race tunnel that delivers water to a power house with six turbine generators. The project-affected area covered eight panchayats. SJVNL required 80 hectares of land for building project infrastructure such as offices, power house, dumping sites, and quarry and site establishments. Of this, 50 hectares of state forest land was acquired from the Government of Himachal Pradesh and 30 hectares of private land from 167 landowners in four villages of three panchayats in Kullu and Shimla districts.